NMR in the time domain: A new methodology to detect adulteration of diesel oil with kerosene. (15th February 2016) - Cunha, Danyelle A.; Montes, Luciana F.; Castro, Eustáquio V.R.; Barbosa, Lúcio L.
Abstract: Petroleum products such as LPG (cooking gas), kerosene, gasoline, diesel oil, among others, are obtained from the refining of crude oil. Among these, the diesel has great importance in the Brazilian road system where fuel consumption leads the rankings in the road sector in Brazil. The high consumption (approximately 50% of total) makes this fuel target to adulteration by irregular products like kerosene, which has low cost and good miscibility with the fuel. Adulteration causes irreparable damage to the car, such as sudden drops in engine, difficulties in starting, increased fuel consumption, degradation of machine performance and environmental harm as emissions of particulate matter during the combustion. This study proposes a new methodology, the nuclear magnetic resonance in the time domain (TD-NMR) to detect the adulteration of four commercial diesel oils with kerosene. Results of the study show that the diesel oil has a transverse relaxation time ( T 2 ) around 0.67 s, while the adulterant kerosene is 1.33 s, and the adulterated samples in the range of 5–100% presented T 2 between 0.67 and 1.33 s. The TD-NMR methodology proposed showed excellent agreement with quantification of adulterant content detected by mid-infrared (MIR) which is the standard technique to detect non-compliance of fuel.